Recycling Waste Soils for Stability Enhancement in Bored Pile Construction - Feng Li; Lei Zhang; Zhengzhen Wang; Qiqi Liu; Tiantao Su; Jinke Wang (Buildings)
Instability in the hole wall of bored pile may cause serious environmental problems. Therefore, using the small hole expansion theory and elastic–plastic theory, we studied the instability mechanism of the hole wall of bored pile, determined the stress expansion solution of the soil layer after the excavation of pile holes in the semi-infinite elastic soil layer, and established a mechanical model. Then, the stability of the hole wall of bored pile in the cohesive soil layer and sandy soil layer was analyzed, and a formula for calculating pile hole wall stability was obtained. Finally, the stability of the hole wall of bored pile under the action of mud slurry was calculated, and the stress on the pile hole wall was analyzed when local instability and overall instability occurred, respectively. The results show that in a sandy soil layer, the safety factor of the hole wall of bored pile has no connection with the depth of the pile hole but is related to the density of mud slurry in the pile hole. In unstable soil layers, the pile hole wall was prone to instability, and the stability of the hole wall could be improved by appropriately increasing the gravity of mud slurry. With the increase in pile diameter, the lateral displacement and deformation of the hole wall increase, and the displacement of the soil layer increases when the hole wall is unstable, increasing the possibility of forming variable cross-section piles correspondingly.